2012
DOI: 10.1002/ceat.201100675
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Operating Conditions and Powder Properties on Pneumatic Conveying Characteristics of a Top Discharge Blow Tank

Abstract: The effects of fluidizing and pressurizing gas flow rates on pneumatic conveying characteristics such as powder mass flow rate, solid-gas ratio, and voidage in a top discharge blow tank pneumatic conveying system are evaluated. Pulverized coal and glass beads were used to investigate the effect of powder properties on conveying performance. The results indicate that as the fluidizing gas flow rate increases, the powder mass flow rate and the solid-gas ratio increase at first and then decline. As the pressurizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In their study, Xu et al. [14] evaluated the effects of fluidizing and pressurizing gas flow rates on the pneumatic conveying characteristics, considering a top discharge blow tank pneumatic conveying system as the investigation object. The results indicated that the increase in the fluidizing gas flow rate leads to an increase in the powder mass flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Xu et al. [14] evaluated the effects of fluidizing and pressurizing gas flow rates on the pneumatic conveying characteristics, considering a top discharge blow tank pneumatic conveying system as the investigation object. The results indicated that the increase in the fluidizing gas flow rate leads to an increase in the powder mass flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…This technology requires pulverized coal to be pneumatically conveyed to the gasifier at high pressure, usually above 3 MPa, which differs from traditional pressure conveying systems in terms of flow speed, solid-phase concentration, flow patterns and stability, etc . Therefore, it has been extensively studied both experimentally and theoretically in recent years, on the topics of pressure drop prediction, effects of operating conditions or material properties, , flow stability, ,,, and flow regimes. ,, …”
Section: Introductionmentioning
confidence: 99%
“…5 This technology requires pulverized coal to be pneumatically conveyed to the gasifier at high pressure, usually above 3 MPa, 6−9 which differs from traditional pressure conveying systems in terms of flow speed, solid-phase concentration, flow patterns and stability, etc. 10 Therefore, it has been extensively studied both experimentally and theoretically in recent years, on the topics of pressure drop prediction, 11−13 effects of operating conditions or material properties, 14,15 flow stability, 6,7,16,17 and flow regimes. 8,9,18 Phase diagrams can well describe flow characteristics of pneumatic conveying by exhibiting the relationship between pressure drops and the superficial gas velocity, which provides an economic and feasible method for flow regime identification, stability analysis, and system optimization.…”
Section: Introductionmentioning
confidence: 99%